Energy Prices and Economic Growth: Theory and Evidence in the Long Run - Ýstemi Berk; Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2013)
In this paper, we attempt to derive and test the role of energy prices on economic growth. We first developed a two-sector endogenous growth model, based on Rebelo (1991). We modified the model such that consumption goods sector uses energy as an input along with capital. The model allows us to show that the growth rate of energy price has a negative effect on the growth rates of energy use and real GDP, consistent with the finding of van Zon and Yetkiner (2003), who studied a similar model by placing energy as an input in the intermediate goods sector. Following this, derived theoretical relationships between energy prices and economic growth and energy consumption were tested empirically using error-correction based panel cointegration tests and panel Autoregressive Distributed Lag (ARDL) approach. We applied this methodology on annual data of composite energy prices, GDP per capita and energy consumption per capita for fifteen countries for the period between 1978 and 2011. We found significant cointegration between energy prices and real GDP per capita as well as between energy prices and energy consumption per capita. Moreover, long-run elasticity estimates reveal a negative and significant impact of composite energy prices on both GDP per capita and energy consumption per capita.
Keywords: O4; Q3; C3; 330; Two-sector model; energy price; endogenous growth; panel cointegration; panel ARDL; Energiepreis; Wirtschaftswachstum; Mehrsektoren-Modell; Endogenes Wachstumsmodell; Kointegration; Panel; Welt